Immunohistochemistry in district general hospitals in England and Wales. Issue 11 (November 1987) - Hall, P A; Domizio, P; Slavin, G; Levison, D A
Abstract : The findings of a survey on the use of immunohistochemistry in district general hospitals in England and Wales are reported. Immunohistochemistry is used in most district hospitals, contributes to the accuracy and objectivity of some histopathological diagnoses, and is considered to be generally useful though not without drawbacks. Its expansion is being hindered by lack of funds for reagents and staff. In a few regions attempts are being made to rationalise expenditure and coordinate development of the service. We believe that if this can be done at a regional or national level then the relatively small cost entailed will be justified by a resulting improvement in the quality of patient care.